Analysis Of Language Errors At The Morphological Level In Anecdote Text Writing Of Class X Students MP (Marketing Management) Of SMK Negeri 3 Balikpapan Academic Year 2023/2024 - Prasetya, Kiftian Hady; Utami, Kasrini Pujining; Indriawati, Prita; Munirah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this study was to determine the location of language errors in writing students' anecdotal texts, especially at the morphological level. The method used in this study is qualitative descriptive. The data collection technique used in this study was by giving assignments in the form of written text to class X MP (Marketing Management) students. The analysis in this study is by utilizing tables so that the analysis is more systematic and neat. The results showed that there are some students who still make mistakes in language, especially at the morphological level, which focuses on the removal of affixes, sounds that should not be melted, melting sounds that should not be melted, morpheme replacement, improper use of basic words, and improper repetition of words.